Seismic Performance and Failure Mechanisms of Reinforced Concrete Structures Subject to the Earthquakes in Türkiye - Işık, Ercan; Avcil, Fatih; Hadzima-Nyarko, Marijana; İzol, Rabia; Büyüksaraç, Aydın; Arkan, Enes; Radu, Dorin; Özcan, Zeki (Sustainability, 2024)
Many reinforced-concrete structures collapsed or were seriously damaged in the 7.7 and 7.6 magnitude earthquakes that occurred in southern Türkiye on 6 February 2023. The recorded peak ground accelerations were quite high (2.2 g) and the recorded motions’ elastic acceleration response spectra were significantly greater than the elastic design spectra given by the most recent Turkish seismic design code. A total of 518,000 houses were heavily damaged or collapsed in the eleven cities affected by the earthquake. More than 53,000 people lost their lives and over 100,000 people were injured, the majority of these injurits caused by the collapse of reinforced concrete structures. Post-earthquake damage assessments are important in the context of applying sustainability principles to building design and construction. In this study, post-earthquake damage assesments and evaluations were made for the reinforced-concrete structures that were exposed to destruction or various structural damage in Hatay, Kahramanmaraş and Adıyaman, which where most affected after the Kahramanmaraş earthquakes. The RC building damage and failure mechanisms resulting from field observations were evaluated in detail from a broad performance-based structural and earthquake engineering perspective. Information about Kahramanmaraş earthquakes is given briefly. Design spectra and spectral accelerations were compared for the earthquake stations in these three provinces. Soft/weak story, short column, insufficiently reinforced-concrete, and poor workmanship are the primary causes of structural damage, which cause earthquake weaknesses in these buildings.